FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG DI BEKASI - Haryodewanto, Bernardus Yudhistira; Triandewo, Maris Agung (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The main purpose of this study was to determine the effect of Luxury Brand Perception, Social Influence and Brand Personality on Purchase Intention of Samsung smartphone brands in Bekasi. This study uses a type of quantitative research. The data is supported by distributing questionnaires to 200 respondents by using Likert scale. This study uses the Partial Least Square method. The results of this study indicate that Luxury Brand Perception has no effect on Purchase Intention on the Samsung smartphone brand in Bekasi. The biggest possibility to explain this is the customer's perception of Samsung brand smartphones that don't really consider luxury goods. Although customers feel that the Samsung brand is attractive, impressive and has the best quality, customers do not really feel that the brand is a unique brand, moreover luxurious. However, the Social Influence and Brand Personality variables have an effect on Purchase Intention on the Samsung smartphone brand in Bekasi.